Konsep Supervisi Pendidikan dan Pengawasan Internal-Eksternal dalam Kurikulum Merdeka di Sekolah Dasar - Ferra Dian Oktaviani; Evita Puspita Dewi; Nurul Maharani; Tantri Pramadita; Dimas Raskian Aji; Bahtiyar Heru Susanto (Journal Innovation In Education, 2024)
The concept of educational supervision includes the understanding, objectives, functions, principles, and internal-external supervision. A supervisor is someone who is in charge of supervising, coaching, directing and solving problems that exist within the school and outside the school. Educational supervision can improve the professional ability of teachers, principals, and other education personnel so that the education process runs according to what has been planned before. The research was conducted through a qualitative approach with data collection techniques, literature studies were then presented in the form of descriptive narratives.